Conductive paste containing ruthenium oxide and preparation method thereof

Through the synergistic effect of nano-scale ruthenium oxide powder, carbon nanotubes and specific solvents, the problems of ruthenium oxide powder agglomeration and uneven mixing are solved, and a conductive paste with high conductivity and good stability is prepared, which is suitable for the manufacture of high-precision electronic devices.

CN120613173AActive Publication Date: 2025-09-09XIAN TENGXING ELECTRONIC TECH CO LTD

Patent Information

Application Number
CN202511113334.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-11
Publication Date
2025-09-09
Estimated Expiration
2045-08-11

AI Technical Summary

Technical Problem

Existing ruthenium oxide powder is prone to agglomeration during the preparation process, resulting in uneven distribution of powder particle size, making it difficult to form a uniform and dense conductive network. In addition, it is difficult to achieve sufficient and uniform mixing of ruthenium oxide powder and other components in the existing conductive slurry during the mixing and dispersion process, affecting the conductive performance and stability. Improper addition of auxiliary conductive agents also affects the slurry performance.

Method used

Nano-scale ruthenium oxide powder and carbon nanotubes are used as the conductive phase, combined with glass powder PbO-B2O3-SiO2 as the binding phase, a mixed solvent of terpineol and butyl carbitol in a specific proportion, ammonium polyacrylate as a dispersant and dibutyl phthalate as a plasticizer, and ball milling and ultrasonic dispersion processes are used to prepare a conductive slurry with uniform dispersion and good stability.

Benefits of technology

It achieves high conductivity (resistivity as low as 85.5 mΩ/sq@20μm, 30%-50% lower than the control example), excellent dispersibility (slurry stability > 5 months), and low-temperature adaptability (matching the low-temperature sintering process of 500-600℃), making it suitable for the manufacture of high-precision electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120613173A_ABST
    Figure CN120613173A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of conductive paste preparation, and particularly discloses conductive paste containing ruthenium oxide and a preparation method of the conductive paste. The conductive paste is prepared from the following components in percentage by mass: 40 percent to 50 percent of ruthenium oxide, 3.8 percent to 5 percent of carbon nano tubes, 5 percent to 10 percent of PbO-B2O3-SiO2, 3 percent to 8 percent of ethyl cellulose, 21 percent to 28 percent of terpilenol, 9 percent to 12 percent of butyl carbitol, 0.7 percent to 1 percent of ammonium polyacrylate and 1 percent to 2 percent of dibutyl phthalate. According to the preparation method, ruthenium oxide is activated in vacuum, a mixed solvent is combined after dispersion, and a ball milling and ultrasonic dispersion synergistic process is adopted, so that the slurry is uniformly dispersed and has excellent stability. According to the invention, a ruthenium oxide-carbon nanotube-frit ternary synergistic system is constructed, and terpilenol and butyl carbitol in a specific mass ratio are taken as a mixed solvent, so that the problems of insufficient conductivity and easy agglomeration of traditional paste are effectively solved, and the method can be widely applied to manufacturing of high-precision electronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of conductive paste preparation, and in particular relates to a conductive paste containing ruthenium oxide and a preparation method thereof. Background Art

[0002] Conductive pastes, as key functional materials in the electronic materials field, are widely used in the manufacture of numerous electronic components, including thick-film circuits, resistors, capacitors, and solar cells. Their performance directly impacts the electrical performance, reliability, and stability of these components. With the rapid advancement of electronic technology, performance requirements for conductive pastes are increasing. Driven particularly by the demand for high-precision, high-performance electronic components, the development of conductive pastes with excellent conductivity, good dispersibility, and stable rheological properties has become a key research direction in the industry.

[0003] Ruthenium oxide (RuO2), as an important conductive phase material, has attracted considerable attention in the field of conductive pastes due to its unique physical and chemical properties. Ruthenium oxide exhibits high electrical conductivity, excellent chemical and thermal stability, and can maintain stable electrical properties over a wide temperature range, making it an ideal choice for preparing high-performance conductive pastes, especially for resistor pastes requiring high resistance stability.

[0004] However, the current technology for preparing ruthenium oxide-based conductive pastes still faces numerous challenges. For one thing, the preparation process for ruthenium oxide powder significantly impacts its final performance. In traditional preparation methods, ruthenium oxide powders tend to agglomerate during synthesis, resulting in an uneven particle size distribution. This agglomerated powder, when added to the conductive paste, makes it difficult to form a uniform, dense conductive network, thus affecting the conductive properties and stability of the paste.

[0005] The preparation process for conductive pastes is also crucial. Existing conductive paste preparation methods often struggle to achieve a fully uniform mixing of ruthenium oxide powder and other components during the mixing and dispersion process. This is particularly true when mixing ruthenium oxide powder with components such as the binder and solvent. Due to the significant differences in the physicochemical properties of these components, delamination and agglomeration are prone to occur, resulting in poor rheological properties of the paste, making it difficult to meet the requirements of printing and coating processes.

[0006] Furthermore, to reduce costs and further enhance the performance of conductive pastes, auxiliary conductive agents are often added. However, selecting the appropriate auxiliary conductive agent and controlling its addition amount to achieve a synergistic conductive effect with ruthenium oxide while not affecting the overall performance of the paste remains a challenge facing current preparation technologies. While carbon nanotube auxiliary conductive agents can effectively enhance conductivity, adding too much can lead to excessive viscosity, impacting processability; while adding too little can undermine their auxiliary conductive properties.

[0007] There is an urgent need to develop more preparation methods to address the deficiencies in the existing technology and to prepare conductive slurries containing ruthenium oxide that have excellent performance, high stability, and are suitable for industrial production. Summary of the Invention

[0008] To solve the above technical problems, the present invention uses nano-scale ruthenium oxide powder and carbon nanotubes as the conductive phase, glass powder PbO-B2O3-SiO2 (the softening temperature matches the substrate sintering temperature) and ethyl cellulose as the binding phase, a mixture of terpineol and butyl carbitol in a specific ratio as the mixed solvent, ammonium polyacrylate as the dispersant, and dibutyl phthalate as the plasticizer. Through formulation research and process optimization, a conductive slurry containing ruthenium oxide with uniform dispersion, good stability and excellent conductive properties is obtained.

[0009] On the one hand, the present invention provides a conductive paste containing ruthenium oxide, which is composed of the following components by mass percentage: 40%-50% of ruthenium oxide, 3.8%-5% of carbon nanotubes, 5%-10% of PbO-B2O3-SiO2, 3%-8% of ethyl cellulose, 21%-28% of terpineol, 9%-12% of butyl carbitol, 0.7%-1% of ammonium polyacrylate, and 1%-2% of dibutyl phthalate.

[0010] Furthermore, in the conductive paste, the conductive paste is composed of the following components in mass percentage: 50% ruthenium oxide, 5% carbon nanotubes, 10% PbO-B2O3-SiO2, 3% ethyl cellulose, 21% terpineol, 9% butyl carbitol, 1% ammonium polyacrylate, and 1% dibutyl phthalate.

[0011] In a second aspect, a method for preparing the conductive paste of the present invention is also provided, comprising the following steps: S1. Drying the ruthenium oxide powder under vacuum at 180-210° C. for 2-3 hours to obtain activated ruthenium oxide; S2, cooling the activated ruthenium oxide prepared in S1 to room temperature and mixing it with ammonium polyacrylate, and dispersing it ultrasonically at 42-45 kHz for 30-35 minutes to prepare a ruthenium oxide-ammonium polyacrylate composite dispersion system; S3, mixing terpineol and butyl carbitol to prepare a mixed solvent; S4, adding the PbO-B2O3-SiO2, carbon nanotubes and ruthenium oxide-ammonium polyacrylate composite dispersion system into a mixed solvent, and ball milling for 4-5 hours to obtain a ball milled mixture; S5, ultrasonically dispersing the ball-milled mixture obtained in S4 to obtain a finely dispersed mixture; S6. Add ethyl cellulose and dibutyl phthalate to the finely dispersed mixture prepared in S5, stir, and sieve to prepare a conductive slurry containing ruthenium oxide.

[0012] Furthermore, in the method, the particle size of the ruthenium oxide powder in S1 is 50-100 nm.

[0013] Furthermore, in the method, the mass ratio of terpineol to butyl carbitol in S3 is 7:3.

[0014] Furthermore, in the method, the carbon nanotubes in S4 have a diameter of 10-20 nm and an aspect ratio of 50-100.

[0015] Furthermore, in the method, the ball milling in S4 is performed using zirconia balls at a rotation speed of 300-350 rpm.

[0016] Furthermore, in the method, the ultrasonic power of the ultrasonic dispersion in S5 is 500W, and the ultrasonic dispersion time is 20-30min.

[0017] Furthermore, in the method, in S6, the stirring is magnetic stirring, and the stirring temperature is 60-65°C.

[0018] Finally, the invention also provides the use of the conductive paste in the preparation of electronic components.

[0019] Compared with the prior art, the technical solution provided by the present invention has at least the following beneficial effects or advantages: (1) High conductivity: Through the synergistic effect of RuO2 and CNT, the slurry resistivity is as low as 85.5mΩ / sq@20μm, which is 30%-50% lower than the control.

[0020] (2) Excellent dispersibility: Vacuum activated RuO2 combined with ball milling and ultrasonic two-step dispersion process avoids filler agglomeration, and the slurry stability is greater than 5 months.

[0021] (3) Low temperature adaptability: The specific glass material (PbO-B2O3-SiO2) and the mixed solvent formed by mixing terpineol and butyl carbitol in a specific mass ratio work synergistically to match the low temperature sintering process of 500-600℃.

[0022] (4) Process compatibility: Ethyl cellulose and plasticizer optimize the rheological properties of the conductive paste of the present invention, making it suitable for precision devices such as thick film circuits and solar cells.

[0023] The present invention solves the problems of insufficient conductivity and easy agglomeration of traditional slurries by combining a ternary synergistic system of ruthenium oxide, carbon nanotubes, and glass frit and a specific solvent ratio with a specific conductive slurry preparation process of the present invention, and is suitable for the manufacture of high-precision electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0025] The technical solutions of the present invention are described below with reference to the following embodiments; however, the present invention is not limited to the following embodiments.

[0026] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below with reference to specific embodiments and drawings, but the embodiments are not intended to limit the present invention.

[0027] The experimental methods and detection methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are commercially available unless otherwise specified.

[0028] Example 1 This embodiment is to prepare a conductive paste containing ruthenium oxide.

[0029] In this embodiment, the carbon nanotubes are multi-walled carbon nanotubes with a diameter of 10 nm and an aspect ratio of 50; the particle size of ruthenium oxide (RuO2) is 50 nm; the PbO in PbO-B2O3-SiO2 is 60 wt%, B2O3 is 20 wt%, and SiO2 is 20 wt%; the process flow chart is as follows: Figure 1 shown.

[0030] The conductive paste containing ruthenium oxide is composed of the following components by mass percentage: 40% ruthenium oxide (RuO2), 4% carbon nanotubes (CNTs), 5% PbO-B2O3-SiO2, 8% ethyl cellulose, 28% terpineol, 12% butyl carbitol, 1% ammonium polyacrylate, and 2% dibutyl phthalate.

[0031] Weigh each component according to the above composition, and prepare a conductive paste containing ruthenium oxide according to the following steps: S1. Dry the RuO2 powder in vacuum at 200°C for 2.5 hours to reduce surface adsorbed water and obtain activated RuO2; S2, cooling the activated ruthenium oxide prepared in S1 to room temperature and mixing it with ammonium polyacrylate, and dispersing it ultrasonically at 42 kHz for 30 minutes to prepare a ruthenium oxide-ammonium polyacrylate composite dispersion system; S3, mixing terpineol and butyl carbitol, stirring and mixing to prepare a mixed solvent; S4, adding the PbO-B2O3-SiO2, carbon nanotubes and ruthenium oxide-ammonium polyacrylate composite dispersion system into a mixed solvent, and ball milling using zirconium oxide balls at a speed of 300 rpm for 4 h to obtain a ball-milled mixture; S5, dispersing the ball-milled mixture obtained in S4 by ultrasonication at 500W for 20 minutes to obtain a finely dispersed mixture; S6. Add ethyl cellulose and dibutyl phthalate to the finely dispersed mixture prepared in S5, stir magnetically at 60°C for 2 hours, and pass through a 400-mesh sieve to obtain a conductive slurry containing ruthenium oxide, which is marked as conductive slurry #1.

[0032] Example 2 This embodiment is to prepare a conductive paste containing ruthenium oxide.

[0033] In this embodiment, the carbon nanotubes are multi-walled carbon nanotubes with a tube diameter of 15 nm and an aspect ratio of 80; the particle size of ruthenium oxide (RuO2) is 70 nm; and the PbO-B2O3-SiO2 contains 60 wt% of PbO, 20 wt% of B2O3, and 20 wt% of SiO2.

[0034] The conductive paste containing ruthenium oxide is composed of the following components, calculated by mass percentage: 44% ruthenium oxide (RuO2), 3.8% carbon nanotubes (CNTs), 8% PbO-B2O3-SiO2, 7% ethyl cellulose, 24.5% terpineol, 10.5% butyl carbitol, 0.7% ammonium polyacrylate, and 1.5% dibutyl phthalate.

[0035] Weigh each component according to the above composition, and prepare a conductive paste containing ruthenium oxide according to the following steps: S1, vacuum drying RuO2 powder at 180℃ for 3 hours to reduce surface adsorbed water and obtain activated RuO2; S2, cooling the activated ruthenium oxide prepared in S1 to room temperature and mixing it with ammonium polyacrylate, and ultrasonicating at 45 kHz for 32 minutes to prepare a ruthenium oxide-ammonium polyacrylate composite dispersion system; S3, mixing terpineol and butyl carbitol, stirring and mixing to prepare a mixed solvent; S4, adding the PbO-B2O3-SiO2, carbon nanotubes and ruthenium oxide-ammonium polyacrylate composite dispersion system into a mixed solvent, and ball milling using zirconium oxide balls at a rotation speed of 320 rpm for 4.5 h to obtain a ball-milled mixture; S5, dispersing the ball-milled mixture obtained in S4 by ultrasonication at 500W for 25 minutes to obtain a finely dispersed mixture; S6. Add ethyl cellulose and dibutyl phthalate to the finely dispersed mixture prepared in S5, stir magnetically at 65°C for 2.5 hours, and pass through a 400-mesh sieve to obtain a conductive slurry containing ruthenium oxide, which is marked as conductive slurry #2.

[0036] Example 3 This embodiment is to prepare a conductive paste containing ruthenium oxide.

[0037] In this embodiment, the carbon nanotubes are multi-walled carbon nanotubes with a tube diameter of 20 nm and an aspect ratio of 100; the particle size of ruthenium oxide (RuO2) is 100 nm; and the PbO-B2O3-SiO2 contains 60 wt% of PbO, 20 wt% of B2O3, and 20 wt% of SiO2.

[0038] The conductive paste containing ruthenium oxide is composed of the following components in percentage by mass: 50% ruthenium oxide (RuO2), 5% carbon nanotubes (CNTs), 10% PbO-B2O3-SiO2, 3% ethyl cellulose, 21% terpineol, 9% butyl carbitol, 1% ammonium polyacrylate, and 1% dibutyl phthalate.

[0039] Weigh each component according to the above composition, and prepare a conductive paste containing ruthenium oxide according to the following steps: S1. Dry the RuO2 powder in a vacuum at 210°C for 2 hours to reduce surface adsorbed water and obtain activated RuO2.

[0040] S2, cooling the activated ruthenium oxide prepared in S1 to room temperature and mixing it with ammonium polyacrylate, and ultrasonicating at 42 kHz for 35 minutes to prepare a ruthenium oxide-ammonium polyacrylate composite dispersion system; S3, mixing terpineol and butyl carbitol, stirring and mixing to prepare a mixed solvent; S4, adding the PbO-B2O3-SiO2, carbon nanotubes and ruthenium oxide-ammonium polyacrylate composite dispersion system into a mixed solvent, and ball milling using zirconium oxide balls at a speed of 350 rpm for 5 h to obtain a ball-milled mixture; S5, dispersing the ball-milled mixture obtained in S4 by ultrasonication at 500W for 30 minutes to obtain a finely dispersed mixture; S6. Add ethyl cellulose and dibutyl phthalate to the finely dispersed mixture prepared in S5, stir magnetically at 62°C for 3 hours, and pass through a 400-mesh sieve to obtain a conductive slurry containing ruthenium oxide, which is marked as conductive slurry #3.

[0041] Comparative Example 1 In this comparative example, 30% terpineol was used instead of the mixed solvent of 21% terpineol and 9% butyl carbitol, and the remaining components and preparation conditions were the same as those in Example 3. The obtained conductive paste was labeled as Comparative Example 1#.

[0042] Comparative Example 2 In this comparative example, 30% butyl carbitol was used to replace the mixed solvent of 21% terpineol and 9% butyl carbitol, and the remaining components and preparation conditions were the same as those in Example 3. The obtained conductive paste was labeled as comparative example 2#.

[0043] Comparative Example 3 In this comparative example, 3% of polyvinyl pyrrolidone was used to replace 3% of ethyl cellulose, and the remaining components and preparation conditions were the same as those in Example 3. The prepared conductive paste was labeled as Comparative Example 3#.

[0044] Test Case In this test example, conductive films were made from the conductive pastes 1-3# prepared in Examples 1-3 and the conductive pastes 1#-3# of the contrast agents prepared in Comparative Examples 1-3. The resistivity of the conductive films was measured using a four-probe method to evaluate the conductive properties of different conductive pastes.

[0045] The conductive paste stability test method is to place the conductive paste at room temperature, visually observe whether the conductive paste agglomerates, and record the time. The test results are shown in Table 1.

[0046] Table 1 Performance test results of different conductive pastes

[0047] Note: Regarding resistivity, for example, 128.9 mΩ / sq@20μm means: for a square film of this material with a thickness of 20μm, the resistance between opposite sides is 128.9 mΩ; 98.7 mΩ / sq@20μm means: for a square film of this material with a thickness of 20μm, the resistance between opposite sides is 98.7 mΩ.

[0048] The results show that the resistivity of the conductive film prepared by the 1#-3# conductive pastes prepared in Examples 1-3 is 85.5-98.7 mΩ / sq@20μm, which is significantly lower than the resistivity of the conductive film prepared by the conductive pastes prepared in Comparative Examples 1-3, which is 128.9-183.4 mΩ / sq@20μm. This indicates that the electronic paste prepared by the mixed solvent of terpineol and butyl carbitol has better conductive performance than the electronic paste prepared by using a single solvent terpineol, a single solvent butyl carbitol, and a conductive paste prepared by replacing ethyl cellulose with polyvinyl pyrrolidone, indicating that the components of the conductive paste containing ruthenium oxide provided by the present invention have a synergistic effect.

[0049] The stability of the conductive paste prepared in Examples 1-3 (>5-6 months) is better than that of Comparative Examples 1-3 (only >3 months), indicating that the specific mixed solvent of terpineol and butyl carbitol in the present invention is compatible with ethyl cellulose, and the conductive paste has better stability.

[0050] The preparation method provided by the present invention first activates ruthenium oxide by vacuum drying, removes physically adsorbed moisture on the surface of ruthenium oxide, and reduces surface hydroxyl groups, thereby exposing more metal active sites. This further forms a bridging network with CNTs with a high aspect ratio, fills the gaps in the conductive path, reduces contact resistance, and improves conductivity efficiency, with a resistivity as low as 85.5mΩ / sq@20μm. Terpineol improves the stability of the conductive slurry, while butyl carbitol improves leveling. The specific ratio of the two optimizes the rheological properties of the conductive slurry. The dispersant and the ball milling and ultrasonic multi-step dispersion process synergistically improve the uniformity of the components in the slurry and enhance the stability of the slurry. This solves the technical problems of insufficient conductivity and easy agglomeration of traditional slurries.

[0051] As described above, the basic principles, main features and advantages of the present invention are well described. The above embodiments and descriptions are merely descriptions of preferred embodiments of the present invention, and the present invention is not limited to the above embodiments. Various changes and improvements made to the technical solutions of the present invention by those skilled in the art without departing from the spirit and scope of the present invention should fall within the scope of protection determined by the present invention.

Claims

1. A conductive paste containing ruthenium oxide, characterized in that The conductive paste is composed of the following components by mass percentage: 40%-50% ruthenium oxide, 3.8%-5% carbon nanotubes, 5%-10% PbO-B2O3-SiO2, 3%-8% ethyl cellulose, 21%-28% terpineol, 9%-12% butyl carbitol, 0.7%-1% ammonium polyacrylate, and 1%-2% dibutyl phthalate.

2. The conductive paste according to claim 1, characterized in that The conductive paste is composed of the following components by mass percentage: 50% ruthenium oxide, 5% carbon nanotubes, 10% PbO-B2O3-SiO2, 3% ethyl cellulose, 21% terpineol, 9% butyl carbitol, 1% ammonium polyacrylate, and 1% dibutyl phthalate.

3. The method for preparing the conductive paste according to claim 1, characterized in that: The following steps are involved: S1. Drying the ruthenium oxide powder under vacuum at 180-210° C. for 2-3 hours to obtain activated ruthenium oxide; S2, cooling the activated ruthenium oxide prepared in S1 to room temperature and mixing it with ammonium polyacrylate, and dispersing it ultrasonically at 42-45 kHz for 30-35 minutes to prepare a ruthenium oxide-ammonium polyacrylate composite dispersion system; S3, mixing terpineol and butyl carbitol to prepare a mixed solvent; S4, adding the PbO-B2O3-SiO2, carbon nanotubes and ruthenium oxide-ammonium polyacrylate composite dispersion system into a mixed solvent, and ball milling for 4-5 hours to obtain a ball milled mixture; S5, ultrasonically dispersing the ball-milled mixture obtained in S4 to obtain a finely dispersed mixture; S6. Add ethyl cellulose and dibutyl phthalate to the finely dispersed mixture prepared in S5, stir, and sieve to prepare a conductive slurry containing ruthenium oxide.

4. The method according to claim 3, characterized in that The particle size of the ruthenium oxide powder in S1 is 50-100 nm.

5. The method according to claim 3, characterized in that The mass ratio of terpineol to butyl carbitol in S3 is 7:

3.

6. The method according to claim 3, characterized in that The carbon nanotubes in S4 have a diameter of 10-20 nm and an aspect ratio of 50-100.

7. The method according to claim 3, characterized in that The ball milling in S4 is performed using zirconia balls at a rotation speed of 300-350 rpm.

8. The method according to claim 3, characterized in that The ultrasonic power of the ultrasonic dispersion in S5 is 500W, and the ultrasonic dispersion time is 20-30min.

9. The method according to claim 3, characterized in that In the step S6, the stirring is magnetic stirring, and the stirring temperature is 60-65°C.

10. Use of the conductive paste according to claim 1 or claim 2 in the preparation of electronic components.

Citation Information

Patent Citations

  • Process for preparing conductive slurry for crystalline silicon solar cell front electrode

    CN102097183A

  • Electroconductive slurry for front electrode of solar battery and preparing method of electroconductive slurry

    CN103177793A

  • Zinc ion hybrid capacitor based on ruthenium oxide / carbon material composite positive electrode and construction method thereof

    CN112466677A

  • Resistance paste with low temperature coefficient

    CN113793715A

  • Bus electrode paste

    KR1020100067824A

Cited By

  • Low-cost silver paste and preparation method and application thereof

    CN121260555A

  • A low-cost silver paste, its preparation method and application

    CN121260555B